The Paradox of Informal Economy in Urban Area Indonesia: A Case Study Street Vendors in Jalan Salemba Raya, Jakarta, and Jalan Raya Sawangan, Depok - Fathy, Rusydan; Rachmawan, Dicky (Masyarakat: Jurnal Sosiologi, 2020)
Informal economic has a big proportion which absorbs 58% of the workforce in Indonesia. In urban areas, it easily can be seen as street vendors (SV). Several previous studies on informal economic about street vendors see them from negative perspective (as the source of urban irregularity) and positive perspective (for contribution to national economic development). By using the literature review, observation, and depth interview with the SV at Jalan Salemba Raya (Jakarta City) and Jalan Raya Sawangan (Depok City), this article particularly shows with the second perspective of previous studies that SV contributes to economic activity in urban. The conversion of SV capitals (social, cultural, and economic) in adaptation effort with using technology (internet) are modes of survival in economic competition and technological changes.